2022
DOI: 10.1038/s41467-022-30003-5
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in homologous recombination repair genes in prostate cancer brain metastases

Abstract: Improved survival rates for prostate cancer through more effective therapies have also led to an increase in the diagnosis of metastases to infrequent locations such as the brain. Here we investigate the repertoire of somatic genetic alterations present in brain metastases from 51 patients with prostate cancer brain metastases (PCBM). We highlight the clonal evolution occurring in PCBM and demonstrate an increased mutational burden, concomitant with an enrichment of the homologous recombination deficiency muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Somatic missense mutations in Plexin-B1 have been detected in patient samples of prostate cancer metastases (26). Recent studies have shown a PLXNB1 mutation rate of around 5% (ranging from 3.3% (27), 3.4% (28), 4.9% (29), to 7.8% (30) (cBioportal), compared to 9.8%, 6.8%, 2.4% and 13.7% in PTEN in the same studies. Functional analysis in vitro of three such mutations (T1697A, T1795A, L1815P), demonstrated that these sequence changes inhibit the interaction of Rnd1, Rac and R-Ras with Plexin-B1 and block the ability of Plexin-B1 to mediate R-Ras inactivation (26,31).…”
Section: Introductionmentioning
confidence: 76%
“…Somatic missense mutations in Plexin-B1 have been detected in patient samples of prostate cancer metastases (26). Recent studies have shown a PLXNB1 mutation rate of around 5% (ranging from 3.3% (27), 3.4% (28), 4.9% (29), to 7.8% (30) (cBioportal), compared to 9.8%, 6.8%, 2.4% and 13.7% in PTEN in the same studies. Functional analysis in vitro of three such mutations (T1697A, T1795A, L1815P), demonstrated that these sequence changes inhibit the interaction of Rnd1, Rac and R-Ras with Plexin-B1 and block the ability of Plexin-B1 to mediate R-Ras inactivation (26,31).…”
Section: Introductionmentioning
confidence: 76%
“…Interestingly, MEnZn‐CuO NPs were found for the first time as metal nanoparticles to negatively regulate the expression of HR repair pathway genes in tumors with defective HR repair capacity. However, our current study has not yet identified the targets of MEnZn‐CuO NPs to regulate the HR repair in tumor cells 50 . Homologous recombination deficiency (HRD) is the first phenotypically defined predictive marker for therapy with PARP inhibitors in ovarian cancer.…”
Section: Discussionmentioning
confidence: 95%
“…The HR repair plays an important role in the combination strategy of PARP inhibitors. Mutations in the key HR repair pathway genes BRCA1, BRCA2, and ATM are often critical for PARP inhibitor sensitization 47–50 . It has been reported that CDK4/6 inhibitors can induce DNA damage and genomic instability, which in turn can have a synthetic lethal effect with PARP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While intraductal variant and neuroendocrine differentiation are suggestive of an underlying HRD mutation, they have no predictive capacity over or independent of genomic testing. [76][77][78][79][80] While the usage of platinum sensitivity as a marker of BRCAness is established in serous ovarian carcinoma, extrapolation of the same to carcinoma prostate is challenging since platinum-based chemotherapy is not a standard frontline option. However, two series have reported impressive outcomes in carcinoma prostate HRD patients when treated with platinum-based therapy.…”
Section: Hunting For Additional Biomarkersmentioning
confidence: 99%